Design and Implementation of Access Door Control with Mo-bile Alert - Nwogu, Chijioke; Eze, Monday; Okunbor, Charles (International Journal of Engineering and Technology, 2020)
The necessity for adequate security of lives and properties cannot be overemphasized. Tackling insecurity in an effective manner calls for active computer-based researches and solutions. Essentially a security system is designed to help detect intrusion and prevent unauthorized access. These security threats are tracked by installing various security access doors and alarm systems. Findings have shown that many access doors use either password or biometric form of authentication separately which are easily compromised. This paper presents a two level automated access control for door security with mobile alert system, powered by a 5V, 6000mAH battery. In addition a multi factor authentication using biometrics (fingerprint) and password was also used to enhance access control for this system. A mobile phone call alert and alarm system was uniquely included to this design to notify owners of the presence of an intruder when multiple attempts of incorrect login credentials are presented to the system over a short period of time. The program for the microcontroller was written in C language. This paper concluded that the use of multi factor authentication with mobile phone call alert will help improve the security for access doors used in banks, residential buildings, hospitals, military properties and other institutions and where confidentiality and restrictions are needed.